Youtube Como Rede Social: Contribuições Da Plataforma Para A Aprendizagem De Língua Inglesa (PERcursos Linguísticos, 2020)
This Work aims at investigating the YouTube platform as a social media and an useful space to an autonomous English language learning. This research is not intended to claim that the availability of quality material online is sufficient to provide more autonomy to the students. We believe that YouTube is a potential platform to enhance autonomy, but we are aware that there is a specific kind of student who could benefit from using this tool. For the theoretical basis of this research we will have the meaning of social network as in Recuero (2009) and we will seek, mainly in Leffa (2003), Paiva (2005) and Wisniewska (1998), a starting point to understand how the autonomy in learning occurs.